The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.21203/rs.3.rs-2609919/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Examination of alternative eGFR definitions on the performance of deep learning models for detection of chronic kidney disease from fundus photographs

Abstract: Deep learning (DL) models have shown promise in detecting chronic kidney disease (CKD) from fundus photographs. However, previous studies have utilized a serum creatinine-only estimated glomerular rate (eGFR) equation to determine CKD despite the existence of more accurate methods. In this study, we used the UK Biobank as a test and validation dataset to demonstrate an incremental and statistically significant improvement in model performance for predicting CKD when using a creatinine and cystatin C eGFR equat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…33,40 Prior retinal AI studies have focused primarily on predicting chronic kidney disease based on eGFR only. [17][18][19] Here we show that retinal BioAge is predictive of higher prevalence of chronic kidney disease using the KDIGO criteria (i.e., eGFR and UACR). In contrast, retinal BioAge was not predictive in UK Biobank, where the overall prevalence of chronic kidney disease was very low (~5%).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…33,40 Prior retinal AI studies have focused primarily on predicting chronic kidney disease based on eGFR only. [17][18][19] Here we show that retinal BioAge is predictive of higher prevalence of chronic kidney disease using the KDIGO criteria (i.e., eGFR and UACR). In contrast, retinal BioAge was not predictive in UK Biobank, where the overall prevalence of chronic kidney disease was very low (~5%).…”
Section: Discussionmentioning
confidence: 87%
“…10,11 We and others have shown that these DL models can detect cardiovascular risk, chronic kidney disease, and diabetic retinopathy. [12][13][14][15][16][17][18][19][20][21] DL models analyzing retinal images have also been developed to estimate "biological age. "…”
Section: Introductionmentioning
confidence: 99%